Desalted duck egg white nanogels combined with κ‐carrageenan as stabilisers for food‐grade Pickering emulsion. (28th October 2021) - Zhao, Jingyun; Dai, Yalei; Gao, Jin; Deng, Qianchun; Wan, Chuyun; Li, Bin; Zhou, Bin
Summary: There was an extensive interest in food‐grade Pickering emulsions formulated by natural stabilisers owing to the gradual growing demand for pursuing green‐label products. Based on this, the desalted duck egg white nanogels (DEWN) combined with κ‐carrageenan (CAR) (CAR/DEWN) were used as stabilisers to prepare environment‐friendly Pickering emulsions. The DEWN and CAR/DEWN as well as the particles‐stabilised emulsions were all characterised. Compared with the DEWN‐ and CAR‐stabilised emulsions, Pickering emulsions based on CAR/DEWN were investigated to illustrate the long‐term stability according to the results of visual appearance, static multiple light scattering and centrifugation experiments. In addition, CAR/DEWN could prepare stable high internal phase emulsions, which may give a new perspective for nutraceutical or drug encapsulation and delivery. Adding CAR to the DEWN not only increased the apparent viscosity of the emulsions to 122.2% but also enhanced the thixotropic recovery rate to 87.7%. In general, CAR/DEWN as stabilisers significantly promoted the Pickering emulsions' properties, and provided a possibility for the application of Pickering emulsion in foods. Abstract : The desalted duck egg white nanogels combined with κ‐carrageenan canb be used as stabilisers to prepare food‐grarde Pickering emulsions. The Pickering emulsions showed long‐term stability and increasing properties.